Effective management strategies in primary health clinics for promoting patient loyalty: A literature review - Afira Febriani Surya Wijaya; Vip Paramarta; Farida Yuliaty; Kosasih Kosasih; Firda Nur Laila (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: In the context of increasing competition within the healthcare sector, patient loyalty has emerged as a vital determinant of the long-term viability of primary healthcare clinics. Purpose: To explore and assess evidence-based management strategies that effectively foster patient loyalty. Method: A systematic literature review was conducted following the PRISMA framework, utilizing five prominent electronic databases and focusing on publications from 2020 to 2025. Results: Patient loyalty is significantly influenced by factors such as healthcare provider communication, service quality, patient satisfaction, clinic reputation, and marketing efforts. The findings suggest that the integration of these five elements forms the most effective strategic framework for enhancing patient loyalty. Conclusion: It is recommended that primary healthcare clinics implement targeted interventions, including structured communication training for staff, regular service quality assessments, systematic patient feedback collection, strategic reputation management, and comprehensive marketing initiatives to strengthen patient loyalty.